Treating Heart Inflammation With Interleukin-1 Blockade in a Case of Erdheim–Chester Disease - Tomelleri, Alessandro; Cavalli, Giulio; De Luca, Giacomo; Campochiaro, Corrado; D’Aliberti, Teresa; Tresoldi, Moreno; Dagna, Lorenzo (Frontiers in Immunology, 2018)
ABSTRACT Pericarditis is an inflammatory heart disease, which may be idiopathic or secondary to autoimmune or autoinflammatory diseases and often leads to severe or life-threatening complications. Colchicine and non-steroidal anti-inflammatory drugs represent the mainstay of treatment, whereas use of corticosteroids is associated with recurrence of disease flares. While effective and safe anti-inflammatory therapies remain an unmet clinical need, emerging clinical and experimental evidence point at a promising role of inhibition of the pro-inflammatory cytokine interleukin 1 (IL-1). We thus evaluated treatment with the IL-1 receptor antagonist anakinra in a case of extremely severe pericarditis with cardiac tamponade and failure secondary to Erdheim-Chester disease (ECD), a rare clonal disorder of macrophages characterized by rampant inflammation and multi-organ involvement. A 62-year-old man was admitted to the Emergency Department with severe pericardial effusion requiring the creation of a pleuro-pericardial window. A whole-body contrast-enhanced computed tomography pointed at a diagnosis of ECD with involvement of the heart and pericardium and of the retroperitoneal space. Over the following days, an echocardiography revealed a closure of the pleuro-pericardial window and a relapse of the pericardial effusion. Treatment with anakinra, the recombinant form of the naturally occurring IL-1 receptor antagonist, was started at a standard subcutaneous dose of 100 mg/day. After two days we observed a dramatic clinical improvement, an abrupt reduction of the inflammatory markers and a reabsorption of the pericardial effusion. Anakinra was maintained as monotherapy, and the patient remained asymptomatic in the absence of disease flares for the following 1 year. Recent studies point at inhibition of IL-1 activity as an attractive treatment option for patients with refractory idiopathic recurrent pericarditis. Anakinra may also have a role in patients with pericarditis in the setting of systemic inflammatory disorders, such as ECD.